Impact of ankle injuries on joint range of motion and muscle viscoelasticity in female amateur volleyball athletes - Sung, E. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Introduction This study aimed to compare ankle joint range of motion (ROM) and muscle viscoelastic properties in female amateur volleyball players with a history of ankle sprain (AS group) and without (non-AS group).